Critical Review of the Journey of Democracy in Indonesia: Functions and Authorities of the Regional Representative Council (DPD) in the Constitutional System - Maximus Dorisara (Syntax Corporation Indonesia, 2024)
The aim of this research is to analyze and explain the function and authority of the Regional Representative Council (DPD) in the Indonesian constitutional system and to see objectively how the function and authority of the Regional Representative Council (DPD) is implemented according to the Indonesian constitution. This research uses descriptive normative law to explain the function and role of regional representative bodies in the constitutional system. Normative legal research only uses literature studies to collect data.